OPPORTUNITIES, RISKS AND STRATEGIES TO MINIMIZE THE RISK FINTECH LENDING: STUDY META SYNTHESIS - Panglipursari, Dwi Lesno (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2022)
This study aims to configure by identifying opportunities, risks and strategies to minimize the risk ofthe existence of fintech lending as a financial intermediary institution using a meta-synthesis methodological approach. The number of articles sampled as much as 29 articles. The results show that business and investment opportunities in this sector are indicated by a large market share, the number of repeat borrowers, an element of trust between borrowers and lenders, a technology-based and uncomplicated loan system and without business guarantees. While the risk indicated by weaknesses in credit management or credit management is a risk that really needs to be considered, including in determining interest rates, and determining borrowers to be funded without credit analysis considerations. The strategy needed is to use a low interest rate strategy, a better management management strategy, a strategy to capture opportunities as well as a collaboration and growth strategy, as well as the need for the Government to make clear and centralized regulations and P2P platforms. Keywords: Opportunity, Risk, Fintech Lending Strategy, Meta Synthesis.